Cryptolepine and Nibima inhibit hepatitis B virus replication - Seth A. Domfeh; Patrick W. Narkwa; Osbourne Quaye; Kwadwo A. Kusi; Odalys Rivera; Martin M. Danaah; Baba A.N. Musah; Gordon A. Awandare; Kwesi B. Mensah; Mohamed Mutocheluh (Scientific African, 2021)
The continuous use of interferons (IFNs) in patients with chronic hepatitis B virus (HBV) infection leads to myriad adverse effects. Also, in sub-Saharan Africa where chronic HBV infection is endemic, pegylated IFN-α and tenofovir disoproxil fumarate, which are first-line agents in the treatment of chronic HBV infection, are inaccessible due to their associated high cost. Hence, there is a need for other cheaper sources of therapies that are less toxic and readily available. In this study, we investigated the anti-HBV activity of cryptolepine and a cryptolepine-based preparation (Cryptolepis sanguinolenta) locally called Nibima. The anti-HBV activity of cryptolepine was established in human hepatoma cells (HepG2 cells) transfected with pHBV1.3 in the presence of cryptolepine and/or IFN-α. The quantity of HBV-DNA and antigens (HBeAg, HBcAg and HBsAg) secreted into the culture supernatant were assessed by qPCR and ELISA, respectively. To translate our in vitro findings into clinical care, a 49-year-old male patient with a history of chronic HBV infection was administered with Nibima for 6 months in a case study, and HBV load, as well as haematological, kidney and liver function indices, were assessed. Cryptolepine reduced HBV-DNA in a dose-dependent manner in vitro, and the magnitude of the reduction was enhanced by the presence of a low concentration of IFN-α. The levels of HBV core protein, HBsAg and HBeAg were similarly reduced in a dose-dependent manner. After 6 months of Nibima therapy, the HBV load of the patient reduced from 10.4 × 104 IU/mL to 8.6 × 102 IU/mL (about 99% reduction). More so, there were no reported abnormalities in the haematological, liver and kidney function indices within the 6 months of the Nibima therapy. Our results suggest that cryptolepine inhibits HBV-DNA replication, and could be substituted for human IFN-α. Also, a clinical trial of Nibima should be conducted for potential use as an effective and cheaper therapeutic agent for the management of chronic HBV infection in resource-limited countries such as Ghana.